ChemInform Abstract: Synthesis of Chlorophyll Derivatives Possessing a Mono/Bi/Terpyridinyl Group at the C3‐Ethynyl Terminal and Optical Properties of the π‐Conjugates. Issue 34 (26th August 2014) - Yamamoto, Youhei; Tamiaki, Hitoshi
Abstract The synthesis of eight of the title compounds is presented (three examples are shown in the scheme).